Modeling the resilience of startups in the COVID-19 pandemic using the system dynamics approach - Mahdi Homayounfar; Faezeh Kamali-Chirani; Adel Pourghader Chobar; Amir Daneshvar (Journal of Safety Science and Resilience, 2025)
The COVID-19 pandemic has profoundly impacted startups, disrupting operations, consumer behavior, and market dynamics. Addressing these challenges necessitates an in-depth analysis of startups' vulnerabilities and the development of effective strategies to bolster their resilience and sustainability. This study introduces a combined thematic analysis and system dynamics approach to enhance startups' resilience during the pandemic. A qualitative thematic analysis was employed to identify the key factors influencing resilience. Semi-structured interviews with 12 experts provided data categorized into 21 themes across four dimensions: team, founder, human resources, and startup characteristics. Building on the qualitative phase, a system dynamics model was developed, comprising 32 auxiliary variables, five flow variables, four constants, and four stock variables. Four scenarios were devised to evaluate resilience within this model, reflecting varying degrees of financial strength, government support, and crisis management improvements. The results highlight the effectiveness of Scenario 4, which achieved the highest resilience improvement, driven by a 5 % increase in financial strength, a 5 % increase in government support, and a 10 % enhancement in crisis management. These findings offer critical insights for stakeholders and researchers seeking to strengthen startup resilience during crises.